Effect of Salt Stress on Cytosine Methylation within GL2, An Arabidopsis thaliana Gene Involved in Root Epidermal Cell Differentiation. Absence of Inheritance in the Unstressed Progeny - Beyrne, Cecilia Carmen (2019)
Methylation/demethylation of cytosines is an epigenetic strategy for transcriptional regulation, allowing organisms to rapidly respond and adapt to different stimuli. In this context, and using Arabidopsis thaliana as a plant model, we explored whether an environmental stress is sufficient to trigger a change in the methylation status of Glabra-2, a master gene associated with root epidermal cell differentiation. As this gene acts mainly in the epidermis in the root, we examined the stress-driven methylation levels specifically in that tissue. We focused on the stress caused by different salt concentrations in the growth medium. When testing the effect of 20 and 75 mM NaCl, we found that there is a significant decrease in the CG methylation level of the analyzed genomic region within the epidermis. Whereas this reduction was 23% in mildly stressed plants, it turned out to be more robust (33%) in severely stressed ones. Notably, this latter epigenetic change was accompanied by an increase in the number of trichoblasts, the epidermal cell type responsible for root hair development. Analysis of an eventual inheritance of epigenetic marks showed that the non-stressed progeny (F1) of stressed plants did not inherit-in a Lamarckian fashion-the methylation changes that had been acquired by the parental individuals.